2018
DOI: 10.3390/app9010081
|View full text |Cite
|
Sign up to set email alerts
|

Permeability and Leaching Properties of Recycled Concrete Aggregate as an Emerging Material in Civil Engineering

Abstract: In this article, a study of the threshold gradient and leaching properties for recycled material, namely, recycled concrete aggregate (RCA), was conducted. The RCA in this study is a material that comes from recycling concrete debris. A series of tests in permeameter apparatus in a constant head manner were conducted. The test method has been improved to eliminate common mistakes, which occur when the constant head method is used. During the following study, aggregates with gradations equal to 0–8, 0–16, and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…It can also be observed that the density of the recycled aggregates decreases, which is due to the porous mortar adhered to them. The values of the void ratio, porosity, and therefore hydraulic conductivity, in the case of RA are higher than a natural aggregate [19].…”
Section: Materials and Mixturesmentioning
confidence: 76%
“…It can also be observed that the density of the recycled aggregates decreases, which is due to the porous mortar adhered to them. The values of the void ratio, porosity, and therefore hydraulic conductivity, in the case of RA are higher than a natural aggregate [19].…”
Section: Materials and Mixturesmentioning
confidence: 76%
“…Other uses of the RCA include: roads substructures, earth dam construction [35][36][37], paving blocks and structural blocks and bricks manufacture [37,38], bituminous-aggregate mixes [39][40][41][42], road pavements [43], self-compacting concrete [44][45][46], polymer concrete [47], shotcrete [48,49], concrete exposed to elevated temperatures [50], soil stabilization [51], pervious concrete [52], reactive powder concrete [53], artificial reef formation [37].…”
Section: Introductionmentioning
confidence: 99%
“…The growing popularity of this material contributes to a better understanding of the properties of this material. Understanding its limitations and recommendations regarding its use already at the stage of the design, then improves the construction works [31].…”
Section: Literature Reviewmentioning
confidence: 99%